PENURUNAN ANGKA PEROKSIDA MINYAK KELAPA TRADISIONAL DENGAN ADSORBEN ARANG SEKAM PADI IR 64 YANG DIAKTIFKAN DENGAN KALIUM HIDROKSIDA - Wahjuni, Sri; Kostradiyanti, Betty (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008, 2012)
Research on IR64 rice shell ash activation with KOH was carried out. Then, this activated ash known as adsorbent was applied to absorb H2O2 solution. This adsorbent was then applied to absorb peroxide number of traditional coconut oil. The research includes activation of rice ash with 5%, 10%, and 15% KOH, followed by determination of rate and isotherm adsorption towards H2O2. Finally, the ash was applied to absorb traditional coconut oil, in order to decrease peroxide number of the oil. Research results indicated that, adsorption rate of the ash with KOH activation is higher than without KOH activation. Adsorption isotherm patern of the ash with and without activation is following Langmuir adsorption. Rice shell ash activated with 15% KOH can increased adsorption capacity of H2O2 about 297.16 mg/g, whereas without activation the adsortion capacity is about 271.66 mg/g. Activated ash with 15% KOH was the applicated to decrease peroxide number of traditional coconut oil. In this study, we obtain that the ash can decreased peroxide number until 84.4%.
Keywords: activated, rice shell ash, adsorbent, adsorption, peroxide number.